The Christian martyr as a hyperthanatic philosopher and mystes, and the success of christianity - Kozłowski, Jan M. (Vox Patrum, 2018)
The creation of the concept of the martyr by ancient Christianity was undoubtedly one of the reasons why this young religion could endure through times of persecution and also attract new believers. But what exactly made this concept so effective? Among the many mutually non-exclusive answers, one more may be provided: the person of the martyr simultaneously fulfilled, on a previously unknown level of intensity and scale, two soteriological ideals of the ancient world, i.e., that of the dying philosopher whose attitude toward death showed that death had no power over him and that of the mystes intimately united with the dying and resurrecting divinity.